2015
DOI: 10.1016/j.expneurol.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol deregulates Mecp2/MeCP2 in differentiating neural stem cells via interplay between 5-methylcytosine and 5-hydroxymethylcytosine at the Mecp2 regulatory elements

Abstract: Methyl CpG Binding Protein 2 (MeCP2) is an important epigenetic factor in the brain. MeCP2 expression is affected by different environmental insults including alcohol exposure. Accumulating evidence supports the role of aberrant MeCP2 expression in ethanol exposureinduced neurological symptoms. However, the underlying molecular mechanisms of ethanolinduced MeCP2 deregulation remain elusive. To study the effect of ethanol on Mecp2/MeCP2 expression during neurodifferentiation, we established an in vitro model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 91 publications
9
62
3
Order By: Relevance
“…Given that the brain tissue in our previous study was collected more than 2 weeks following the last METH exposure, it is possible that the observed decrease in MeCP2 expression was due to METH withdrawal rather than METH intake per se. This effect is consistent with previous findings (Liyanage et al, 2015), and METH withdrawal has been shown to alter the expression of several transcription factors (Cadet et al, 2014). In the present study, tissue was collected immediately following SA, and we did not observe a difference in NAc core MeCP2 expression between the ELS-exposed rats and handled controls in the METH condition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Given that the brain tissue in our previous study was collected more than 2 weeks following the last METH exposure, it is possible that the observed decrease in MeCP2 expression was due to METH withdrawal rather than METH intake per se. This effect is consistent with previous findings (Liyanage et al, 2015), and METH withdrawal has been shown to alter the expression of several transcription factors (Cadet et al, 2014). In the present study, tissue was collected immediately following SA, and we did not observe a difference in NAc core MeCP2 expression between the ELS-exposed rats and handled controls in the METH condition.…”
Section: Discussionsupporting
confidence: 93%
“…In order to investigate potential epigenetic mechanisms underlying ELS-induced increased vulnerability, we focused on striatal MeCP2 because of its established role in drug reward and reinforcement (Deng et al, 2010;Im et al, 2010;Zhang et al, 2014;Liyanage et al, 2015;Hou et al, 2015). The present study replicated our previous findings of ELS-induced increases in METH SA (Lewis et al, 2013;Lewis et al, 2015), which is also consistent with other drugs of abuse (Vazquez et al, 2005;Moffett et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1) in various classes of leukocytes. The binding and activity of MeCP2 appears enhanced at promoter 5hmCG sites in the brain (Zhubi et al, 2014) and its activity is considered particularly important, because in the brain MeCP2 activity responds to external stimuli (e.g., cocaine, ethanol) (Pol Bodetto et al, 2013; Liyanage et al, 2015). MeCP2 binding in the brain to modified C residues can work to enhance transcription if bound to 5hmCG, or repress transcription if bound to 5mCG (Mellen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An article by Liyanage and colleagues (2015) attempted to shed light on the discrepancies between studies on the effects of ethanol on methyl CpG binding protein 2 (MeCP2) expression (Gangisetty et al 2014) while also understanding the molecular mechanisms of DNA methylation at regulatory elements in the MeCP2 gene. Ethanol-induced alterations of methylation can contribute to deregulating MeCP2 expression (Liyanage, Rastegar 2014).…”
Section: Analysis Of Dna Methylation In Models Of Fetal Alcohol Exposurementioning
confidence: 99%